REKOMENDASI PEMINATAN STUDI MENGGUNAKAN METODE K-NEAREST NEIGHBOR DAN FUZZY C-MEANS - Taysa Natalia; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Information Technology Advancements has become inseparable things to human’s life in this modern era, technological advancement has already give positive progress and additional value in educational segment in Indonesia.Technology have role to help undergraduate and college student choose specialization in their field of study respectively, which utilize K-Nearest Neighbor and Fuzzy C-Means Clustering calculation method.Clustering consist of 5 distinct specialization which are DA, IS, R, GD, ACS. Data used in evaluation process are 97 Undergraduate Student with 34 Subject which already decided and 25 Student’s Data to be testing subject.